ANALISIS KINERJA KEUANGAN BERDASARKAN KONSEP VALUE FOR MONEY PADA BLUD PUSKESMAS MURUNG PUDAK KABUPATEN TABALONG - Luthfia Ayu Karina; Wahyu Ramadhani (VALUE, 2021)
Research in quantitative descriptive type with the aim of analyzing the financial performance of public sector organizations using the Value for Money concept at the BLUD Puskesmas Murung Pudak for the period 2016-2020. The research data were analyzed using year-to-year analysis by comparing existing performance reports to overcome fluctuations that occur through measuring the performance of an organization with three main elements, namely Economic Ratios, Efficiency Ratios, and Effectiveness Ratios. The results showed that the financial performance of the Murung Pudak Public Health Center BLUD fluctuated during the study period. The Economic Ratio shows an average of 79% including in Less Economical, the average Efficiency Ratio of 102% is included in the Inefficient category, while the overall Effectiveness Ratio is found to be an average of 97% included in the Effective category.